Design and Implementation of Web-based Collaborative Social Curation - 아바스 알리; Kwon, Yong-Moo; Park, Jaehyuk (PROCEEDINGS OF THE 2014 INTERNATIONAL CONFERENCE ON COLLABORATION TECHNOLOGIES AND SYSTEMS (CTS), 2014)
Recently, social network services(SNSs) have become important media to keep in touch with acquaintances as well as to share experiences of daily lives. Through these SNSs, users can directly share photos, opinion and information. In this work, we implemented a web-based collaborative social curation system which can help users to generate a social album about a specific common event. Our social curation system contains four parts: collecting social contents from multiple web services, grouping those contents according to sub-events, organizing the grouped contents with addition of explanatory sentences (storytelling), and presentation of the result of storytelling phase. In each part, our implementation addresses practical solutions to the problems ailing previous contents creation researches as well as services. In addition to the implementation of whole web-based collaborative social curation system, our main contribution can be summarized as 1) collecting and recollecting social media contents from heterogeneous services automatically and 2) providing collaboration environment based on user expertise to construct a meaningful story.